PNIPAAm-based biohybrid injectable hydrogel for cardiac tissue engineering. (1st March 2016) - Navaei, Ali; Truong, Danh; Heffernan, John; Cutts, Josh; Brafman, David; Sirianni, Rachael W.; Vernon, Brent; Nikkhah, Mehdi
Graphical abstract: Abstract: Injectable biomaterials offer a non-invasive approach to deliver cells into the myocardial infarct region to maintain a high level of cell retention and viability and initiate the regeneration process. However, previously developed injectable matrices often suffer from low bioactivity or poor mechanical properties. To address this need, we introduced a biohybrid temperature-responsive poly(N-isopropylacrylamide) PNIPAAm–Gelatin-based injectable hydrogel with excellent bioactivity as well as mechanical robustness for cardiac tissue engineering. A unique feature of our work was that we performed extensive in vitro biological analyses to assess the functionalities of cardiomyocytes (CMs) alone and in co-culture with cardiac fibroblasts (CFs) (2:1 ratio) within the hydrogel matrix. The synthesized hydrogel exhibited viscoelastic behavior (storage modulus: 1260 Pa) and necessary water content (75%) to properly accommodate the cardiac cells. The encapsulated cells demonstrated a high level of cell survival (90% for co-culture condition, day 7) and spreading throughout the hydrogel matrix in both culture conditions. A dense network of stained F-actin fibers (∼6 × 10 4  μm 2 area coverage, co-culture condition) illustrated the formation of an intact and three dimensional (3D) cell-embedded matrix. Furthermore, immunostaining and gene expression analyses revealed mature phenotypic characteristics of cardiac cells. Notably, the co-culture group exhibited superior structural organization and cell–cell coupling, as well as beating behavior (average ∼45 beats per min, co-culture condition, day 7). The outcome of this study is envisioned to open a new avenue for extensive in vitro characterization of injectable matrices embedded with 3D mono- and co-culture of cardiac cells prior to in vivo experiments. Statement of Significance: In this work, we synthesized a new class of biohybrid temperature-responsive poly(N-isopropylacrylamide) PNIPAAm–Gelatin-based injectable hydrogel with suitable bioactivity and mechanical properties for cardiac tissue engineering. A significant aspect of our work was that we performed extensive in vitro biological analyses to assess the functionality of cardiomyocytes alone and in co-culture with cardiac fibroblasts encapsulated within the 3D hydrogel matrix.